Driving Assessment 2005 : Proceedings of the 3rd International Driving Symposium on Human Factors in Driver Assessment, Trainin 2005
DOI: 10.17077/drivingassessment.1151
|View full text |Cite
|
Sign up to set email alerts
|

Visual Field Defects and the Risk of Motor Vehicle Collisions Among Patients with Glaucoma

Abstract: Summary:This study sought to evaluate the association between visual field defects in the central 24° field and motor vehicle collisions (MVC) among patients with glaucoma. A case-control study was conducted on glaucoma patients aged 55 and older being treated at three university-affiliated eye care practices. Cases were patients who sustained a police-reported motor vehicle collision (MVC); controls were those who did not experience a MVC. For each patient, an Advanced Glaucoma Intervention Study (AGIS) score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 7 publications
4
36
2
Order By: Relevance
“…This is in contrast to other studies that have reported elevated rates for those with such impairments (Haymes, LeBlanc, Nicolela, Chiasson & Chauhan, 2007; McGwin, Xie, Mays, Joiner, DeCarlo, Hall & Owsley, 2005; Rubin et al, 2007). In the case of Rubin et al (Rubin et al, 2007) as with Johnson and Keltner (1983), the association was specific to those with binocular field loss.…”
Section: Visual Function and Drivingcontrasting
confidence: 99%
See 1 more Smart Citation
“…This is in contrast to other studies that have reported elevated rates for those with such impairments (Haymes, LeBlanc, Nicolela, Chiasson & Chauhan, 2007; McGwin, Xie, Mays, Joiner, DeCarlo, Hall & Owsley, 2005; Rubin et al, 2007). In the case of Rubin et al (Rubin et al, 2007) as with Johnson and Keltner (1983), the association was specific to those with binocular field loss.…”
Section: Visual Function and Drivingcontrasting
confidence: 99%
“…In the case of Rubin et al (Rubin et al, 2007) as with Johnson and Keltner (1983), the association was specific to those with binocular field loss. McGwin et al (2005) observed that the association was stronger when considering the extent of impairment in the worse eye. Haymes et al (2007) observed that among glaucoma patients, those with visual field impairment in the worse eye had a nearly five-fold increase in motor vehicle collisions though this association was not statistically significant.…”
Section: Visual Function and Drivingmentioning
confidence: 93%
“…Studies have also shown that glaucoma and/or more advanced VF damage increases the risk of motor vehicle crashes, which reinforces the notion that those with glaucoma may feel (and be) less safe drivers 7,31-33. In one study, worse eye MD was more correlated with crash frequency than better-eye MD, suggesting that unilateral glaucoma may be sufficient to increase accident rates 7. Finally, several papers have provided plausible mechanisms for driving impairment using driving simulators or on-road driving tests.…”
Section: Discussionsupporting
confidence: 64%
“…While some studies suggested that unilateral VF loss is sufficient to cause difficulty driving,29 previous analyses from SEE found that bilateral, but not unilateral, glaucoma was associated with reported difficulty driving at night 4. Studies have also shown that glaucoma and/or more advanced VF damage increases the risk of motor vehicle crashes, which reinforces the notion that those with glaucoma may feel (and be) less safe drivers 7,31-33. In one study, worse eye MD was more correlated with crash frequency than better-eye MD, suggesting that unilateral glaucoma may be sufficient to increase accident rates 7.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation